Estudo das propriedades estruturais, dielétricas e magnéticas do compósito cerâmico (BaFe12O19)x – (BiFeO3)1-x e sua aplicação em dispositivos de radiofrequência e microondas - Rodrigues, Herbert de Oliveira (2014)
The demand for ceramic composite materials for the development of telecommunications systems has been a strong motivator for academic research. Existing technologies can be improved from these researches, and subsequently absorbed by industry and the consumer market. The magnetic and dielectric ceramics have been used in many electronic devices due to the possibility of being designed taking into account certain physical characteristics and its low production cost. The aim of this work consists on the development and characterization of a ceramic composite based on the BiFeO3 (BFO) perovskite and on the BaFe12O19 barium hexaferrite (BaM). The first one is known for its multiferroics properties, while the second is a M-type hexaferrite widely used in various applications. The composite material [(BaFe12O19)x − (BiFeO3)1-x] was produced by the solid state reaction with the use of highenergy mechanical milling and heat treatment. In the synthesis process, it was considered some mole percentages of BFO and BaM. Structural characterization was performed by X-ray Diffraction and Rietveld refinement. Experiments to evaluate the magnetic and dielectric behavior of the samples in the range of Radio Frequency and Microwave as well as simulations of resonators cylindrical antennas by HFSS® software were performed. Studies of the temperature coefficient of capacitance (TCC) and temperature coefficient of resonant frequency (tf) were realized. The composition with x ~ 0.45 showed the best thermal stability (tf ~ 0). The composite material has potential for application in wireless communication systems.